EFFECT OF “PERMATA-KU” EXERCISE ON THE AMPLITUDE OF ACCOMMODATION AND COMPUTER VISION SYNDROME SCORE IN COMPUTER USERS - Azkadina, Amira; Nugroho, Trilaksana; Astuti, Fatimah Dyah Nur; Reki, Winarto; Dharma, Andhika Guna (Majalah Oftalmologi Indonesia, 2023)
Background and Objective: Intense and long-term computer users are at risk of suffering health problems known as computer vision syndrome (CVS) which can have an impact on physical, mental, and economic health. One of the alternative therapies developed is "PERMATA-KU" exercise to reduce complaints related to CVS. The aim of the study was to reveal the effect of "PERMATA-KU" exercise on amplitude of accommodation (AA) and Computer Vision Syndrome scores on computer users. Method: The study of a quasi-experimental with pre-post control design was done. The research subjects were divided into the “PERMATA-KU” exercise group (21 people) and the control group (19 people) with treatment for 4 weeks. CVS scores were measured using the CVS-Questionnaire and monocular AA scores were measured using the push-up method using a Berrens ruler. Mann-Whitney difference test analysis was performed. Results: The exercise group experienced a significant increase in monocular AA value (p=0.010) while the control group experienced a significant decrease in AA (p=0.025). The mean delta of monocular AA values between groups was significantly different after the intervention (p=0.001). There was a significant difference in CVS scores between the postintervention groups (p=0.006) with the mean delta CVS scores between groups being significantly different (p=0.002). There was no correlation between AA scores and CVS scores (p=0.126). Conclusion: "PERMATA-KU" exercise for 4 weeks was shown to significantly increase the value of amplitude of accommodation and decrease CVS scores, but the increase in accommodation amplitude did not correlate with a decrease in CVS scores.